Responses of Grain Yield and Nutrient Content to Combined Zinc and Nitrogen Fertilizer in Upland and Wetland Rice Varieties Grown in Waterlogged and Well-Drained Condition - Supapohn Yamuangmorn (2020)
© 2020, Sociedad Chilena de la Ciencia del Suelo. This study explored the response in grain yield and quality of upland and wetland rice varieties to a combination of zinc (Zn) and nitrogen (N) fertilizers under two water management regimes. A factorial arrangement based on a randomized complete block design composed of three factors was carried out with three independent replications. Upland and wetland rice varieties were grown with three fertilizer treatments; the optimum N rate (86 kg N ha−1) without Zn application, the optimum N rate with Zn (50 kg ZnSO4 ha−1), and the high N rate (172 kg N ha−1) with Zn under waterlogged and well-drained conditions. Grain yield was 27% lower in the well-drained than in the waterlogged condition in wetland rice, while there was no effect in upland rice. Application of optimum N with Zn application produced the highest grain yield in upland rice, while yield was the highest in wetland rice in high N with Zn application. Upland rice grown in the well-drained condition with the optimum and high N with Zn treatments enhanced Zn concentration by 45% and 29% higher than the treatment without Zn, respectively, while it had no difference among three treatments in the waterlogged condition. Wetland rice variety grown under the well-drained condition in optimum and high N rate with Zn treatments were equally effective in improving grain Zn concentration at the average of 88% compared to the control. While rice grown under the waterlogged condition in the high N with Zn treatment had improved 92% the concentration. The optimum N rate with Zn application increased grain yield in upland rice, while the higher N input is required for wetland rice. Grain Zn concentrations of upland and wetland rice varieties were enhanced by applying Zn fertilizer; however, the increased level was depended on N application rate in the individual water condition.